2019
DOI: 10.4102/phcfm.v11i1.1776
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of postnatal care for HIV-positive mothers in the Free State: Nurses’ perspectives

Abstract: Background Postnatal care (PNC) provides the opportunity for protecting the lives of women infected with human immune deficiency virus (HIV) and their babies. The prevention of mother-to-child transmission of HIV (PMTCT) guidelines provide a framework for implementation of PNC. There has been no empirical evidence on how the nurses at the clinic level implement these guidelines. In addition, there are reports that PNC has been neglected in South Africa. Aim The study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(16 reference statements)
5
0
0
Order By: Relevance
“…Sustainability is a limitation of many programs (27) Previous assessments of the model reported concerns around sustainability due to the perception that it increased the workload for staff involved. Similar to our results, stakeholders relevant to implementation of the model into real world practice reported that the expansion of the PNC model could be jeopardized by human resource constraints attributed to strong dependency on externally-funded staff and minimal involvement of non-PNC focused staff (21). Lessons learned from other differentiated models of care provide suggestions on ways to ensure sustainability of the PNCs, including task shifting of some tasks, such as counselling, drug dispensing and administrative tasks, which may be delegated to PNC graduates or PNC members (20).…”
Section: Discussion and Recommendationssupporting
confidence: 87%
See 1 more Smart Citation
“…Sustainability is a limitation of many programs (27) Previous assessments of the model reported concerns around sustainability due to the perception that it increased the workload for staff involved. Similar to our results, stakeholders relevant to implementation of the model into real world practice reported that the expansion of the PNC model could be jeopardized by human resource constraints attributed to strong dependency on externally-funded staff and minimal involvement of non-PNC focused staff (21). Lessons learned from other differentiated models of care provide suggestions on ways to ensure sustainability of the PNCs, including task shifting of some tasks, such as counselling, drug dispensing and administrative tasks, which may be delegated to PNC graduates or PNC members (20).…”
Section: Discussion and Recommendationssupporting
confidence: 87%
“…Our study described similar perceptions of effectiveness as previous studies on implementation of adherence clubs and postnatal groups (21,22). Adherence clubs were highly acceptable to stakeholders, given the observed bene ts, including decongestion of clinics, increased social support for clients and the low cost of implementation (23).…”
Section: Discussion and Recommendationssupporting
confidence: 74%
“…Our study described similar perceptions of effectiveness as previous studies on implementation of adherence clubs and postnatal groups [ 29 , 30 ]. Adherence clubs were highly acceptable to stakeholders, given the observed benefits, including decongestion of clinics, increased social support for clients and the low cost of implementation [ 30 , 31 ].…”
Section: Discussion and Recommendationssupporting
confidence: 78%
“…Our study described similar perceptions of effectiveness as previous studies on implementation of adherence clubs and postnatal groups [ 29 , 30 ]. Adherence clubs were highly acceptable to stakeholders, given the observed benefits, including decongestion of clinics, increased social support for clients and the low cost of implementation [ 30 , 31 ]. An MSF Project report showed that PNC have good early retention in care of the MIP and viral load suppression, as well as zero HIV seroconversion in the infants in similar setting [ 32 ].…”
Section: Discussion and Recommendationssupporting
confidence: 78%
“…The proportion of participants with prior immunization counseling experience in the context of HIV (19.5%) was low, but similar to the figures from Nigerian centers (7.1%-9.1%), 10 , 29 parts of Africa (22-48%) 15 , 30 and elsewhere (36.9%-57.4%). 31 With reports of sub-optimal vaccine responsiveness among HIV-infected infants on ART, 32 health care workers need to pay special attention when counseling women living with HIV on infant immunization.…”
Section: Discussionsupporting
confidence: 65%